Bullwhip Effect Reduction and Improved Business Performance through Guanxi: An Empirical Study - Cao, Qing (2014)
Many operations managers have realized the potential of guanxi to facilitate business transactions. Likewise, operations management researchers have looked at the negative impact caused by the bullwhip effect on excess inventory and the impact of the bullwhip effect on business performance. To date, however, no empirical research has integrated these research streams. Therefore, we draw on both operations strategy literature as well as marketing strategy literature to propose a conceptual model that links guanxi, the bullwhip effect, and business performance in an empirical study. Analysis of our survey data (N=205) using structural equation modeling (SEM) indicates that guanxi has a positive impact on business performance and also reduces the bullwhip effect. We also show how a moderating factor, competition, affects the usefulness of guanxi. Specifically, we provide evidence that the link between guanxi and business performance is weakened by a highly competitive environment.